Forensic accounting and economic value added as panaceas for analysis firm value - Kabir, Musa Usman; Aripin, Norhani; Al-Dhamari, Redhwan Ahmed Ali (2017)
Purpose - In spite of the comprehensiveness of the International Financial Reporting Standards (IFRS) in ensuring fair value accounting.There are still few loopholes in the accounting standards which provide sufficient opportunities for financial statement manipulations (Ikpefan, & Akande 2012).Thus, this practice undermine the “true and fair” view of the financial statement as a result of manipulating financial accounting records for selfish economic aggrandisement within the purview of applicable laws and prevailing accounting standards..The objectives of this paper is to examine the role of forensic accounting and economic value added in analysis the corporate value of firms.Mehodology - The conceptual framework sees forensic accounting practices and economic value added as the antecedent variables and the firm value as the outcome variable. The framework highlight the relationship between value relevance determinants such as forensic accounting and economic value added and the firm value of corporate firms.It emphasis the employment of forensic accounting practices and the analysis of the economic value added as the means by which the real value of firm can be assessed. Findings - The paper shown that forensic accounting practices and economic value added measures are basic remedy for fraudulent financial statement practices because of their invulnerability to the practice of creative accounting.